Probing DNA ‐ Transcription Factor Interactions Using Single‐Molecule Fluorescence Detection in Nanofluidic Devices. Issue 4 (2nd September 2021) - Fontana, Mattia; Ivanovaitė, Šarunė; Lindhoud, Simon; van der Wijk, Elmar; Mathwig, Klaus; Berg, Willy van den; Weijers, Dolf; Hohlbein, Johannes
Abstract: Single‐molecule fluorescence detection offers powerful ways to study biomolecules and their complex interactions. Here, nanofluidic devices and camera‐based, single‐molecule Förster resonance energy transfer (smFRET) detection are combined to study the interactions between plant transcription factors of the auxin response factor (ARF) family and DNA oligonucleotides that contain target DNA response elements. In particular, it is shown that the binding of the unlabeled ARF DNA binding domain (ARF‐DBD) to donor and acceptor labeled DNA oligonucleotides can be detected by changes in the FRET efficiency and changes in the diffusion coefficient of the DNA. In addition, this data on fluorescently labeled ARF‐DBDs suggest that, at nanomolar concentrations, ARF‐DBDs are exclusively present as monomers. In general, the fluidic framework of freely diffusing molecules minimizes potential surface‐induced artifacts, enables high‐throughput measurements, and proved to be instrumental in shedding more light on the interactions between ARF‐DBDs monomers and between ARF‐DBDs and their DNA response element. Abstract : The transcription of genes is regulated by proteins that interact with specific sequences on genomic DNA. Here, fluidics and single‐molecule detection are combined to study interactions between plant transcription factors of the auxin response family and DNA oligonucleotides in vitro. Using independent readouts of diffusivity and energy transfer, the binding of unlabeled auxin response factor to fluorescently labeled DNA is confirmed.